2017
DOI: 10.1371/journal.pone.0183083
|View full text |Cite
|
Sign up to set email alerts
|

Colonization prevalence and antibiotic susceptibility of Group B Streptococcus in pregnant women over a 6-year period in Dongguan, China

Abstract: This study investigated the prevalence of recto-vaginal Group B Streptococcus (GBS) colonization, serotype distribution, and antimicrobial susceptibility patterns among pregnant women in Dongguan, China. Recto-vaginal swabs were collected from pregnant women at gestational age 35-37 weeks between January 1 st 2009 and December 31 st 2014. Isolates were serotyped by latex-agglutination and were tested against seven antimicrobials by disk diffusion. Of 7,726 pregnant women who completed GBS testing, 636 (8.2%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
4
25
0
1
Order By: Relevance
“…Our study demonstrates that the GBS colonization rate in pregnant Chinese women in Liuzhou was 6.1%, which is similar to the reported rate of 7.1% in Beijing [ 9 ] and 8.2% in Dongguan [ 10 ]. Our rate is similar to those of other Asian countries including Philippines (7.5%) [ 11 ], Japan (8.2%) [ 12 ], Myanmar (7.1%) [ 11 ] and South Korea (8.0%) [ 13 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our study demonstrates that the GBS colonization rate in pregnant Chinese women in Liuzhou was 6.1%, which is similar to the reported rate of 7.1% in Beijing [ 9 ] and 8.2% in Dongguan [ 10 ]. Our rate is similar to those of other Asian countries including Philippines (7.5%) [ 11 ], Japan (8.2%) [ 12 ], Myanmar (7.1%) [ 11 ] and South Korea (8.0%) [ 13 ].…”
Section: Discussionsupporting
confidence: 88%
“…ese guidelines generally recommend that pregnant women with S. agalactiae colonization should receive intrapartum antibiotic prophylaxis (IAP) to reduce the incidence of these infections [9,10]. Currently, there are no official guidelines for S. agalactiae screening and prevention in China [5,11]. However, in recent years, S. agalactiae has become an important pathogen in Chinese obstetrics and neonatology [12].…”
Section: Introductionmentioning
confidence: 99%
“…e first-line antibiotic for IAP is penicillin [9,10]; however, since some people are allergic to it, macrolides (e.g., erythromycin) and lincosamides (e.g., clindamycin) are used as the alternative antibiotics [14]. Unfortunately, the resistance of S. agalactiae to macrolides and lincosamides is increasing worldwide [4,9,11,15,16]. Previous studies have shown that the ermB, ermTR, and mefA/E genes are involved in the resistance to macrolides [17], and the linB gene has been linked to the resistance to lincosamides and moderate sensitivity to macrolides [18].…”
Section: Introductionmentioning
confidence: 99%
“…Various standardized phenotypic antimicrobial susceptibility testing methods such as agar diffusion [11], broth microdilution [12], gradient strip tests [13], and disk diffusion [14] have traditionally been used by researchers to determine whether the bacteria are resistant or susceptible. Resistance to specific antibiotics can also be determined by PCR, which investigates the presence or absence of genes responsible for the resistance [15].…”
Section: Introductionmentioning
confidence: 99%